The effects of quality of evidence communication on perception of public health information about COVID-19: Two randomised controlled trials - Claudia R. Schneider (Public Library of Science (PLoS), 2021)
Background The quality of evidence about the effectiveness of non-pharmaceutical health interventions is often low, but little is known about the effects of communicating indications of evidence quality to the public. Methods In two blinded, randomised, controlled, online experiments, US participants (total n = 2140) were shown one of several versions of an infographic illustrating the effectiveness of eye protection in reducing COVID-19 transmission. Their trust in the information, understanding, feelings of effectiveness of eye protection, and the likelihood of them adopting it were measured. Findings Compared to those given no quality cues, participants who were told the quality of the evidence on eye protection was ‘low’, rated the evidence less trustworthy (p = .001, d = 0.25), and rated it as subjectively less effective (p = .018, d = 0.19). The same effects emerged compared to those who were told the quality of the evidence was ‘high’, and in one of the two studies, those shown ‘low’ quality of evidence said they were less likely to use eye protection (p = .005, d = 0.18). Participants who were told the quality of the evidence was ‘high’ showed no statistically significant differences on these measures compared to those given no information about evidence quality. Conclusions Without quality of evidence cues, participants responded to the evidence about the public health intervention as if it was high quality and this affected their subjective perceptions of its efficacy and trust in the provided information. This raises the ethical dilemma of weighing the importance of transparently stating when the evidence base is actually low quality against evidence that providing such information can decrease trust, perception of intervention efficacy, and likelihood of adopting it.